MANFAAT EKOLOGIS DAN FINANSIAL PEMANFAATAN LIMBAH CAIR AGROINDUSTRI SEBAGAI BAHAN BAKU DALAM PRODUKSI BIOGAS UNTUK MEREDUKSI EMISI GAS RUMAH KACA(ECOLOGICAL AND FINANCIAL BENEFITS OF AGRO-INDUSTRIAL WASTEWATER UTILIZATION AS RAW MATER - . Suprihatin (Agromet, 2009)
Agroindustries in general produce a large amount of organic wastewater. Until now, most of this organics waste-stream was not recovered and left to decompose anaerobically in ponds, where it emits methane, a potent greenhouse gas. By anaerobically digesting of the effluents in a suitable bioreactor, methane can be captured and used for combustion in gas engines or boilers. This way, uncontrolled methane emission from the anaerobic decomposition can be avoided and the utilization of fossil fuels can be replaced partly with the renewable biogas from the decomposition process. In addition, the approach of reducing green house gas emission is potentially to earn financial incentive through Clean Development Mechanism project. This paper demonstrates quantitatively some potential ecological and economical benefits derived from utilising agroindustrial effluents by treating it anaerobically to generate biogas (with cases of cane sugar factory, starch industry, palm oil mill, and tofu industry) . As illustration, for each ton cane sugar produced app. 15 m3 methane can be emitted from uncontrolled anaerobic degradation of it wastewater. By capturing the gas and transforming it into renewable biogas, a methane emission of equivalent to ≈ 272 kg CO2 can be avoided and an energy value of app. 427 MJ with a money value of app. Rp 59 600,- can be obtained. In addition, a financial incentive of app. Rp 14 850,- is possible to be earned from clean development mechanism (CDM) project. The ecological and financial benefits derived from anaerobic treatment of agroindustrial wastewater as indicated by this study should therefore become the driving force for the implementation of the approach.